Novel and Nation in the Muslim World
XIV, 226 p.
Keywords: Exploring the relationship between fiction and nation formation in the Muslim world through 12 unique studies from Azerbaijan, Libya, Iran, Algeria, and Yemen, amongst others, this book shows how fiction reflects and relates the complex entanglements of nation, religion, and modernity in the process of political and cultural identity formation.